2015
DOI: 10.1111/and.12402
|View full text |Cite
|
Sign up to set email alerts
|

Varicocele anatomy during subinguinal microsurgical varicocelectomy in Chinese men

Abstract: Knowledge of subinguinal microsurgical varicocelectomy is of fundamental importance to ensure that varicocele is resolved and testicular function is preserved. Our study aimed to describe the number of veins, arteries and lymphatics in the subinguinal spermatic cord and to clarify their differences between two sides, between patients with different complaints and between varicoceles with different clinical grades. A total of 102 consecutive patients underwent 162 primary subinguinal microsurgical varicocelecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
7
0
2
Order By: Relevance
“…Hopps et al ( 2003 ) reported that 43 % of their MSV cases had multiple ISAs and Libman et al ( 2010 ) reported that 50 % of their MSV cases had multiple ISAs. Similarly, Lv et al ( 2015 ) reported that multiple ISAs were identified in 58 % of patients in their varicocele unit. Most studies have only reported the mean number of ISAs, thus it was unclear whether the number of ISAs is associated with the difficulty of the surgery.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Hopps et al ( 2003 ) reported that 43 % of their MSV cases had multiple ISAs and Libman et al ( 2010 ) reported that 50 % of their MSV cases had multiple ISAs. Similarly, Lv et al ( 2015 ) reported that multiple ISAs were identified in 58 % of patients in their varicocele unit. Most studies have only reported the mean number of ISAs, thus it was unclear whether the number of ISAs is associated with the difficulty of the surgery.…”
Section: Discussionmentioning
confidence: 87%
“…Although preservation of the ISA is a key step in MSV, however it is not an easy task due to the multiple ISAs and the complex anatomical relationship between the ISAs and adjacent ISVs (Hopps et al 2003 ; Libman et al 2010 ; Lv et al 2015 ). We found multiple ISAs in 39 % of our MSV procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the greater number of internal spermatic arteries and because these arteries are surrounded by a dense network of adherent veins, the identification of internal spermatic artery pulsation is difficult in the subinguinal and classical inguinal approaches carried out near the external inguinal ring. 15,18,19 In contrast, the number of internal spermatic arteries around the internal inguinal ring was typically one, and the diameter was significantly larger than those of the arteries found at the subinguinal level ( Table 2). These findings are consistent with previous anatomical descriptions.…”
Section: Discussionmentioning
confidence: 97%
“…These findings are consistent with previous anatomical descriptions. 15,18,19 The primary branch point of the testicular artery is usually located along its course through the inguinal canal. Furthermore, the need for a Doppler probe to identify the artery was less frequent with the high inguinal approach (Table 2), which involves the creation of a wide opening in the inguinal canal.…”
Section: Discussionmentioning
confidence: 99%
“…В данный обзор не вхо-дили мужчины с азооспермией, ранее получавших оперативное лечение по поводу варикоцеле. Также в данный обзор не входили исследования мужчин с субклинической степенью варикоцеле [6,7].…”
Section: результатыunclassified